2018
DOI: 10.1007/s00520-018-4205-2
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-pocket expenses experienced by rural Western Australians diagnosed with cancer

Abstract: Rural WA cancer patients experience significant OOPE following their diagnosis. The impact these expenses have on patient wellbeing and their treatment decisions need to be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 26 publications
5
51
0
Order By: Relevance
“…younger age, higher household income and longer distance from treatment centres (Baili et al, 2016;Davidoff et al, 2013;Newton et al, 2018;Pisu, Azuero, Benz, McNees, & Meneses, 2017;Valtorta & Hanratty, 2013). Furthermore, studies have found that low socioeconomic status is a risk factor for unemployment after a cancer diagnosis; for women, a cancer diagnosis results in a higher risk of unemployment, but mainly male cancer patients seem to be affected by a total decline in family income (Torp, Nielsen, Fosså, Gudbergsson, & Dahl, 2013;Zajacova et al, 2015).…”
Section: What This Paper Adds?mentioning
confidence: 99%
See 1 more Smart Citation
“…younger age, higher household income and longer distance from treatment centres (Baili et al, 2016;Davidoff et al, 2013;Newton et al, 2018;Pisu, Azuero, Benz, McNees, & Meneses, 2017;Valtorta & Hanratty, 2013). Furthermore, studies have found that low socioeconomic status is a risk factor for unemployment after a cancer diagnosis; for women, a cancer diagnosis results in a higher risk of unemployment, but mainly male cancer patients seem to be affected by a total decline in family income (Torp, Nielsen, Fosså, Gudbergsson, & Dahl, 2013;Zajacova et al, 2015).…”
Section: What This Paper Adds?mentioning
confidence: 99%
“…In addition to a deeper understanding of the costs that induce financial toxicity, identifying high‐risk patients is important (Carrera et al, ). Medical and non‐medical out‐of‐pocket costs have been found to be higher for patients with, for example, younger age, higher household income and longer distance from treatment centres (Baili et al, ; Davidoff et al, ; Newton et al, ; Pisu, Azuero, Benz, McNees, & Meneses, ; Valtorta & Hanratty, ). Furthermore, studies have found that low socioeconomic status is a risk factor for unemployment after a cancer diagnosis; for women, a cancer diagnosis results in a higher risk of unemployment, but mainly male cancer patients seem to be affected by a total decline in family income (Torp, Nielsen, Fosså, Gudbergsson, & Dahl, ; Zajacova et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This study is the rst to assess the incidence of CHE, associated factors and its coping strategies for cancer care in Ethiopia. The average overall cancer care expenditure was half of the average unadjusted household annual income and nearly three-fourth of the average unadjusted household annual expenditure which is higher as compared to Australian patients [25]. This was however; lower than the ndings of other studies in which patients spent 59.9% of household annual income [19].…”
Section: Discussionmentioning
confidence: 63%
“…A significant number of cancer survivors suffer financial hardship as a consequence of cancer treatment, previously described as 'financial toxicity' [23,24]. Out-of-pocket costs are a concern for cancer patients and recent Australian studies have described these important costs for indigenous vs non-indigenous cancer patients [25], Queenslanders with major cancer [26] and rural Western Australian cancer patients [27]. Other jurisdictions have also noted the financial hardship and high out-of-pocket expenditure due to cancer, such as the US, Germany and Canada [28][29][30].…”
Section: Introductionmentioning
confidence: 99%